Observations on the quill mites (Acari: Syringophilidae) from charadriiform birds - Skoracki, Maciej; Dabert, Jacek; Schmäschke, Ronald (Zootaxa, 2006)
We provide a list of all 19 named species of the family Syringophilidae (Acari: Prostigmata) parasitizing charadriiform birds (Charadriiformes) together with new records and keys to these species. We describe a new species Niglarobia cursoriae sp. nov. from Cursorius temminckii Swainson (Glareolidae) and redescribe Creagonycha totana (Oudemans, 1904) from Tringa totanus L. (Scolopacidae). Niglarobia cursoriae sp. nov. differs from the closely related species N. rhinoptili Fain et al., 2000 in the following characters: in females of N. cursoriae sp. nov. hysterosomal shield is present and fused with pygidial shield; the length ratio of setae g:pg1:pg2 is 1:5:3.8. In females of N. rhinoptili the hysterosomal shield is absent; and the length ratio of setae g:pg1:pg2 is 1:3:2. All known syringophilid records from charadriiform birds are summarized in tabular form.